PERFORMA PEDET SIMMENTAL YANG DIBERI PAKAN SILASE RUMPUT GAJAH DAN RUMPUT GAJAH SEGAR: PERFORMANCE OF SIMMENTAL CALVES FEED WITH ELEPHANT GRASS SILAGE AND FRESH ELEPHANT GRASS - Kardaya, Dede; Nasution, Al humam Nur Kholis; Malik, Burhanudin (Universitas Djuanda, 2024)
This study was conducted to performance of male and female Simmental calves fed elephant grass silage and fresh elephant grass. This research was conducted from April 1 to 30, 2023 at the Center for Superior Livestock Breeding and Animal Feed Greenery Padang Mangatas, West Sumatra. The livestock used in this study were Simmental calves as many as 36. If the treatment results have a significant effect, then the analysis is continued to the Least Significant Difference test. The variables observed in this study were dry matter consumption and body weight gain. Concentrate consumption was significantly different (P<0.05) between males and females only in the silage treatment while for the provision of fresh elephant grass, elephant grass and silage wasnot significantly different (P>0.05). While the FCR of males and females showed results that were not significantly different (P>0.05) between silage, fresh elephant grass, silage and elephant grass. Body weight 14 and body weight 30 on fresh elephant grass rations did not differ significantly (P>0.05) between males and females but for silage, silage and elephant grass there were significant differences (P>0.05) between males and females. For body weight gain in silage and elephant grass, there was a significant difference (P<0.05) between male and female sexes, while male and female sexes did not differ significantly (P>0.05) in silage feed and fresh elephant grass. PBBH showed that the feed treatment gave a significant effect (P<0.05) between males and females on silage feed and elephant grass, while males and females did not differ significantly on silage feed and fresh elephant grass.